2009
DOI: 10.14430/arctic361
|View full text |Cite
|
Sign up to set email alerts
|

Polar Bear Maternal Den Habitat in the Arctic National Wildlife Refuge, Alaska

Abstract: Polar bears (Ursus maritimus) give birth during midwinter in dens of ice and snow. Denning polar bears subjected to human disturbances may abandon dens before their altricial young can survive the rigors of the Arctic winter. Because the Arctic coastal plain of Alaska is an area of high petroleum potential and contains existing and planned oil field developments, the distribution of polar bear dens on the plain is of interest to land managers. Therefore, as part of a study of denning habitats along the entire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 20 publications
1
17
2
Order By: Relevance
“…We calculated that 20 dens could be present in the 1002 Area during any given winter (Appendix A). We allowed simulated dens to occur only on suitable den habitat identified by Durner et al (2006). For each iteration of the model, we randomly distributed the dens across the 1002 Area areas along features identified as denning habitat (Durner et al 2006), with the probability of a den occurring at a given location being proportional to the density of dens predicted by the kernel density map.…”
Section: Den Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…We calculated that 20 dens could be present in the 1002 Area during any given winter (Appendix A). We allowed simulated dens to occur only on suitable den habitat identified by Durner et al (2006). For each iteration of the model, we randomly distributed the dens across the 1002 Area areas along features identified as denning habitat (Durner et al 2006), with the probability of a den occurring at a given location being proportional to the density of dens predicted by the kernel density map.…”
Section: Den Simulationmentioning
confidence: 99%
“…Forwardlooking infrared imagery is a tool that is commonly used to accomplish this task (Amstrup et al 2004). To obtain FLIR imagery, aerial surveys are conducted in December and January with FLIR sensors mounted to either helicopters or airplanes along polar bear denning habitat (Durner et al 2006) in a region of interest. Imagery is monitored real-time and through post hoc review for hotspots that have characteristics consistent with a polar bear den (Amstrup et al 2004).…”
Section: Den Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that wintertime oil and gas exploration and development activities do not disrupt denning and threaten survival of cubs, managers require knowledge of the distribution of the landscape features that are capable of accumulating snow deep enough for pregnant polar bears to dig maternal dens. Photogrammatic techniques have been used to map polar bear denning habitat in the eastern and central portions of the ACP (Durner et al, 2001(Durner et al, , 2006, but the necessary photography has not been available for the western ACP. Here, we present a new method-the automated interpretation of fine-grain digital elevation data-for mapping potential polar bear maternal denning habitat in the coastal regions of the National Petroleum Reserve -Alaska (NPR-A) in the northwest ACP.…”
Section: Introductionmentioning
confidence: 99%
“…Denning habitats include coastal banks, riverbanks, lakeshores, and even some human-made features (Durner et al, 2001(Durner et al, , 2003. On the coastal plain of northern Alaska east of the Colville River, suitable denning habitat comprises less than 1% of the total area (Durner et al, 2001(Durner et al, , 2006), yet approximately 63% of pregnant polar bears in the SB subpopulation rely on terrestrial habitat for maternal denning each winter, and the proportion of on-land denning is increasing (Amstrup and Gardner, 1994;Fischbach et al, 2007). Though most terrestrial denning has occurred within 2 km of the coast (Durner et al, 2003), some polar bear dens have been observed 61 km inland of the Beaufort Sea coast ( Fig.…”
Section: Introductionmentioning
confidence: 99%